2004
DOI: 10.1161/01.cir.0000112571.06979.b2
|View full text |Cite
|
Sign up to set email alerts
|

Single-Wire Pressure and Flow Velocity Measurement to Quantify Coronary Stenosis Hemodynamics and Effects of Percutaneous Interventions

Abstract: Background-Lack of high-fidelity simultaneous measurements of pressure and flow velocity distal to a coronary artery stenosis has hampered the study of stenosis pressure drop-velocity (⌬P-v) relationships in patients. Methods and Results-A novel 0.014-inch dual-sensor (pressure and Doppler velocity) guidewire was used in 15 coronary lesions to obtain per-beat averages of pressure drop and velocity after an intracoronary bolus of adenosine. ⌬P-v relations from resting to maximal hyperemic velocity were construc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
136
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 165 publications
(141 citation statements)
references
References 38 publications
5
136
0
Order By: Relevance
“…For evaluation of the functional severity of coronary stenoses in the clinic (5,20,25), adenosineinduced coronary hyperemia is taken as index for the maximal obtainable conductance induced by increased cardiac work or an ischemic stimulus. In the present study in dog hearts, maximal conductance during peak RH was found to be ϳ25% lower than that obtained during adenosine and the difference was almost gone after treatment of the glycocalyx.…”
Section: Rh Vs Ahmentioning
confidence: 99%
“…For evaluation of the functional severity of coronary stenoses in the clinic (5,20,25), adenosineinduced coronary hyperemia is taken as index for the maximal obtainable conductance induced by increased cardiac work or an ischemic stimulus. In the present study in dog hearts, maximal conductance during peak RH was found to be ϳ25% lower than that obtained during adenosine and the difference was almost gone after treatment of the glycocalyx.…”
Section: Rh Vs Ahmentioning
confidence: 99%
“…11,12 The Doppler sensor-mounted wire (ComboWire; Volcano Corporation, Rancho Cordova, California) has been validated in coronary stenosis evaluation during cardiovascular interventions. 13 Measurements with the ComboWire can be performed during the endovascular treatment of intracranial aneurysms, even in patients with ruptured aneurysms. 12 In these acutely ill patients, PC-MR imaging measurements are usually not feasible.…”
mentioning
confidence: 99%
“…Second, MR appears to be independent of epicardial artery disease. Previous reports (3,30,33) have documented an increase in MR in the presence of an epicardial artery stenosis. From the present study's results, even in the presence of a moderate epicardial stenosis, the increase of NMR could still be used to evaluate the microvascular disruption.…”
Section: H404 Assessment Of Coronary Microcirculation In a Swine Modelmentioning
confidence: 87%